Third mission, university, society: a new relationship model for innovation and social empowerment - Cilona, Chiara (Community Notebook. People, Education and Welfare in the Society 5.0, 2021)
Italian Universities, under some social, cultural and economic pressures, have been called to change the institutional action adding to the two traditional missions, on the one hand the Didactics for a qualified training and on the other the Research, a new objective (called Third Mission ) aimed at continuous interaction with the social environment, school institutions and the business world to create the basis for a common project of development. How has the Italian university paradigm changed? And, above all, how can Universities promote the growth of the person through the acquisition of competence and awareness, and also the constructive dialogue between historically distinct systems: education, research and innovation?